THE MANUFACTURING OF COLD STEEL REINFORCEMENT CLASS V55OA STANDARD ONÖRM B 4707:2010 - T. A. Akhmetov; I. N. Radkova; Y. V. Chikishev; A. V. Kochetkov; L. V. Loktionova (Литьë и металлургия)
The manufacturing technology for wire rod with an optimized chemical composition was developed. It allows to produce reinforced steel class V550A in accordance with the requirements of ONORM B 4707:2010 taking into account changes its quality characteristics after mechanical changes and certify these products on the standard.